Search for dark matter candidates and large extra dimensions in events with a jet and missing transverse momentum with the ATLAS detector - Onofre, A. (2013)
A search for new phenomena in events with a high-energy jet and large missing transverse momentum is performed using data from proton-proton collisions at s√=7 TeV with the ATLAS experiment at the Large Hadron Collider. Four kinematic regions are explored using a dataset corresponding to an integrated luminosity of 4.7 fb−1. No excess of events beyond expectations from Standard Model processes is observed, and limits are set on large extra dimensions and the pair production of dark matter particles.